Treatment of Necrotic Calcified Tooth Using Intentional Replantation Procedure - Nima Moradi Majd; Armita Arvin; Alireza Darvish; Sareh Aflaki; Hamed Homayouni (Case Reports in Dentistry)
Introduction. If the teeth are impacted by a chronic irritant, the pulp space possibly will undergo calcific changes that may impede access opening during root canal treatment. In such cases that conventional endodontic treatment is impossible or impractical, intentional replantation may be considered as a last solution to preserve the tooth. Methods. After failing to perform conventional root canal therapy for a necrotic calcified right mandibular second premolar, the tooth was gently extracted. The root apex was resected and the root end cavity was prepared and filled with calcium enriched mixture (CEM) cement. Then, the extracted tooth was replanted in its original position. Results. After a year the tooth was asymptomatic, and the size of periapical radiolucency was remarkably reduced and no clinical sign of ankylosis was observed. Conclusion. Intentional replantation of the necrotic calcified teeth could be considered as an alternative to teeth extraction, especially for the single-rooted teeth and when nonsurgical and surgical endodontic procedures seem impossible.